Cold-induced anaphylaxis: new insights into clinical and genetic characteristics - Bizjak, Mojca; Korošec, Peter; Košnik, Mitja; Šelb, Julij; Bidovec-Stojkovič, Urška; Svetina, Manca; Zver, Samo; Dinevski, Dejan; Rijavec, Matija (Frontiers in Immunology, 2025)
IntroductionThe pathogenesis of cold urticaria (ColdU) and cold-induced anaphylaxis (ColdA) remains poorly understood, and ColdA is underrepresented in anaphylaxis literature. Laboratory features to guide management are largely unknown. This study evaluated basal serum tryptase (BST) and total immunoglobulin E (IgE) levels in ColdU and ColdA, their associations with clinical features, and the utility of testing for the KIT p.D816V variant in blood leukocytes and hereditary α-tryptasemia (HαT).MethodsNinety-two adults with ColdU were enrolled. ColdA was defined as a reaction involving skin and/or visible mucosal tissue with cardiovascular, respiratory, or gastrointestinal manifestations. Evaluations included patient history, standard cold stimulation testing (sCST) using an ice cube and TempTest®, and laboratory tests.ResultsColdA was diagnosed in 35.9% of patients. ColdU phenotypes based on sCST included typical ColdU (52.2%), localized cold-reflex urticaria (5.4%), and ColdU with negative sCST (42.4%). Negative sCST, compared to typical ColdU, was associated with fewer ColdA cases (p = 0.004) but more spontaneous wheals (p < 0.001). ColdA patients more frequently exhibited generalized wheals (p = 0.047), skin angioedema (p = 0.007), oropharyngeal/laryngeal manifestations (p < 0.001), and itchy earlobes (p = 0.002) than non-ColdA patients. Elevated BST levels (>11.4 ng/mL) in 9.8% of patients were attributed to KIT p.D816V and/or HαT. KIT p.D816V was detected in 6.6% of ColdU and 6.3% of ColdA patients. HαT prevalence was higher in ColdU (10.9%) and ColdA (15.2%) than the general population (estimated at 5.7%; p = 0.041 and p = 0.038). Total IgE levels were significantly higher in ColdA than non-ColdA (p = 0.021).DiscussionThis study confirmed clinical features linked to ColdA previously identified by the multicenter COLD-CE study, including generalized wheals, skin angioedema, oropharyngeal/laryngeal manifestations, and itchy earlobes. We identified new high-risk features. ColdA is more frequently associated with typical ColdU than with ColdU with negative sCST, the latter being linked to spontaneous wheals. ColdA is additionally associated with higher total IgE levels. Furthermore, patients with ColdU and ColdA exhibit higher prevalence of KIT p.D816V and HαT compared to general population data, a finding not previously reported. Further research is needed to explore their clinical implications.